MULTITEXCO - high performance smart multifunctional technical textiles for tensile structures - Heyse, P.; Buyle, G.; Beccarelli, Paolo (Elsevier, 2016)
In recent years, the textile industry developed a new generation of advanced textile materials for the construction sector designed to address the needs of one of the largest markets for textile products. Examples of the advanced textiles developed include fabrics for the rehabilitation of buildings, geotextiles for the consolidation of a wide range of soil structures and the high performance technical textiles for tensile structures. When combine with innovative sensors the fabrics provide an useful tool for the constant monitoring of the structures and can be used to record the mechanical performance or detect anomalies in the expected use of the structures by measuring applied loads, deformations, operating temperatures or other important parameters.